Book Review of "At Risk: Social Justice in Child Welfare and Other Human Services" by Karen J. Swift and Marilyn Callahan, 2009, Toronto: University of Toronto Press - Caitlin Janzen (Social Work & Society, 2009)
The newest book by Canadian social work scholars Karen Swift and Marilyn Callahan is exemplary of how other disciplines can invigorate social work theory. "At Risk" uses child welfare practice as an entry point for exploring the continuing movement away from addressing needs and towards the management of risk in the human services. In "At Risk", Swift and Callahan tease apart the managerial panopticon of the modern child welfare system. That is, the web of surveillance in which families are monitored by child welfare workers who are under the observation of their supervisors; who must answer to regional supervisors; who are accountable to the ministry; which is accountable to the state; which is under the scrutiny of the media; which is assiduous in ensuring that the stories of children who die while in care are never far from the headlines.